Comparison of the participation models of intelligent communities in China and foreign countries: A sample of middle-class-dominated communities - Li, Ziming; Samsurijan, Mohamad Shaharudin (Edelweiss Applied Science and Technology, 2025)
This paper constructs a three-dimensional model of "institution-technology-culture" to compare the participation models of China and foreign countries for the middle-class-dominated smart community. The institutional dimension reveals the difference between the embedded governance (centralization) of Chinese neighborhood committees and the contractual autonomy (decentralization) of Western HOA(Homeowners Association). The technical dimension shows that the technology adoption rate in China (k=0.34h-1) is significantly higher than that in the West (k=0.21h-1). The cultural dimension quantifies the impact: China's government model forms a strong policy response (η=0.41) with the cultural adaptation of high PDI (Power distance index) and LTO (Long-term orientation) (CAI-PDI contribution value 0.2125,Cultural Adaptability Index); its deliberative democracy improves the contribution of social communication (q=0.52) but has higher technological anxiety. The West relies on IDV(Individualism) to drive decentralized decision-making and innovation, but the adoption capacity is limited. The study found that the effectiveness of technological governance is rooted in the cultural cognitive framework. The Chinese model has advantages in organizational efficiency and scale diffusion, while the Western model has more potential for individual empowerment and innovation inclusion. The essence of the difference is the cultural gene projection of collectivist long-term orientation and individualistic instant decision-making.